2017
DOI: 10.1021/acs.biochem.7b00751
|View full text |Cite
|
Sign up to set email alerts
|

Selenoglutathione Diselenide: Unique Redox Reactions in the GPx-Like Catalytic Cycle and Repairing of Disulfide Bonds in Scrambled Protein

Abstract: Selenoglutathione (GSeH) is a selenium analogue of naturally abundant glutathione (GSH). In this study, this water-soluble small tripeptide was synthesized in a high yield (up to 98%) as an oxidized diselenide form, i.e., GSeSeG (1), by liquid-phase peptide synthesis (LPPS). Obtained 1 was applied to the investigation of the glutathione peroxidase (GPx)-like catalytic cycle. The important intermediates, i.e., GSe and GSeSG, besides GSeOH were characterized by Se NMR spectroscopy. Thiol exchange of GSeSG with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 52 publications
(110 reference statements)
2
15
0
Order By: Relevance
“…However, ab initio calculations for selenenyl sulfides 2a and 3a in water showed that, in the most stable conformation, there is no interaction between the SeÀS bond and the amino group, and the LUMO energy levels are almostc omparable with each other (see the SupportingI nformation). The other is the presence of an intramolecular NH···Se hydrogen bond for transienti ntermediate I',a ss hown in Figure 8a, which would suppress the reverse reaction to SeÀS ox and promote the nucleophilic attack of as econd thiol at the S atom to produce intermediate I.I waoka and co-workers previously proposed that as imilar NH···Se hydrogen bond in as elenenyl sulfide speciesc an accelerate cleavage of the SeÀSb ond duringt he GPx-like catalytic cycle of diselenide selenoglutathione( GSeSeG) [17] and dipeptide SecÀCys. [18] Ab initio calculation at HF/6-31 ++G(d,p) in water revealed that the most stable conformation has aN H···Se hydrogen bond for both selenenyls ulfides 12 and 13,a ss hown in Figure 8a.…”
Section: Resultsmentioning
confidence: 99%
“…However, ab initio calculations for selenenyl sulfides 2a and 3a in water showed that, in the most stable conformation, there is no interaction between the SeÀS bond and the amino group, and the LUMO energy levels are almostc omparable with each other (see the SupportingI nformation). The other is the presence of an intramolecular NH···Se hydrogen bond for transienti ntermediate I',a ss hown in Figure 8a, which would suppress the reverse reaction to SeÀS ox and promote the nucleophilic attack of as econd thiol at the S atom to produce intermediate I.I waoka and co-workers previously proposed that as imilar NH···Se hydrogen bond in as elenenyl sulfide speciesc an accelerate cleavage of the SeÀSb ond duringt he GPx-like catalytic cycle of diselenide selenoglutathione( GSeSeG) [17] and dipeptide SecÀCys. [18] Ab initio calculation at HF/6-31 ++G(d,p) in water revealed that the most stable conformation has aN H···Se hydrogen bond for both selenenyls ulfides 12 and 13,a ss hown in Figure 8a.…”
Section: Resultsmentioning
confidence: 99%
“…[26] A striking similarityw ith the repair of misfolded protein with diselenides furthers upports the walkerh ypothesis because this catalytic process hasb een studied in detail and shown to occur also in vivo. [16] However,i ndependent of the mode of action, the superb substrate scope identified in this study togetherw ith the small size, synthetic accessibility,s tability, solubility,l ow toxicity and high efficiency promise that diselenolane-mediated cellular uptake could become quite useful in practice. Particularly interesting is the efficient cytosolic delivery of two orders of magnitude larger substrates like protein-coated quantumd ots (diameter % 15 nm) by the miniscule diselenolanes (diameter % 0.3 nm), as tunning disproportion that is reminiscent of the ant carrying the elephant.…”
mentioning
confidence: 91%
“…Using mostly topics that have been developed recently to characterize the large CPD polymers, [5,6] we here report that cellular uptake of the tiny diselenolanes is compatible with the cytosolic deliveryo fab road variety of functional substrates with diameters up to 15 nm. The combination of this broad substrate tolerance with insights from models tudies call for a mode of action that envisions DiSeL as molecular walkers [15] that move along disulfide tracks in transmembrane proteins, causing temporary local denaturation [16] and the appearance of adaptivem icellar membrane defects. [17] The biotinylated DiSeL tag 8 was synthesized [18] for general non-covalent connection to the substrate through the tetravalent streptavidin (Sav) 9,a% 60 kDa protein ( Figure 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…8), and selenophilicity produces a strong preference for diselenides over mixed selenosulfides. [29][30][31][32][33][34][35][36] As a result, 3-alkyl-1,2diselenolanes prefer to stay closed, and fast exchange makes it challenging to catch selenosulfides and demonstrate that 1,2-diselenolanes really do exchange with thiolates. [27] In the following, this question is clarified, also with regard to post-exchange rearrangements that may or may not account for the intriguing power of 3-alkyl-1,2-diselenolanes to enter into cells.…”
mentioning
confidence: 99%